SOCIAL INEQUALITY THE MIRACLE CELL IN 7 MOVIE - Kristin Lusiana; Bima Prana Chitra (Jurnal Education and Development, 2021)
The problem of the study in this research is: how is the Social Inequality found the Miracle cell in 7 Movie by Lee yoong Goo a man who had disability then, the informants of this research are from the movie miracle cell in 7. The research design used is a qualitative descriptive research method by using Karl marks’s theory.The formulation of the problem in this research is: How do we see the social inequality in the Miracle Cell in 7 film in the character Lee Yoong Go where she has a disability and has nothing, only a 5 year old daughter with her, she is completely innocent and accused charges of murder and rape must bear all of them, just because he could not bring himself to be sentenced to death, from this we learn that today's social gaps still occur a lot in everyday life.The results show that don't slander people arbitrarily even if the person has a disability and has nothing and a father's love is so great for his very big daughter, the truth will be revealed even though the result is always at the end.